Growing up between two cultures : problems and issues of Muslim children - Salili, Farideh; Hoosain, R. (Research in multicultural education and international perspectives., 2014)
This volume deals with social, emotional and educational issues of Muslim children growing up in a Western country. It aims at shedding light on factors that contribute to the successful adjustment of these immigrant children and ways of helping them to adjust to the new life in their new country.